Media Bias - Williams, Mary E., 1960-, editor 454454; Gale Group (Online service) 651863 (Detroit, Michigan : Greenhaven Press, a part of Gale, Cengage Learning, 2011)
This series is inspired by the highly acclaimed Opposing Viewpoints series, which explores important issues, placing expert opinions from a wide range of sources in a unique pro/con format. Like its predecessor, Introducing Issues with Opposing Viewpoints promotes issue awareness as well as critical thinking. Even more user-friendly and accessible than its parent series, it offers a wealth of information at a lower reading level, in a bright, engaging package. This appealing combination helps more students grasp the controversies of our increasingly complex world.